The Involvement of Calcium in the Protective and Toxic (Nonlinear) Responses of Rodent and Human Astroglial Cells - N. Debbie Slamon; Carole Mead; Chris Morgan; Andy Mitchell; Vic W. Pentreath (SAGE Publishing, 2005)
The involvement of [Ca 2+ ] i in the reactive changes of astrocytes which accompany exposure to different chemicals were studied in cultures of C6 and 1321N1 cells. Cells were exposed to up to three serial pulses of the differentiating agent dBcAMP, which induces activation-type changes in the cells. Other cells, with or without the dBcAMP treatments, were treated with a range of concentrations of the antidepressants amitriptyline and fluoxetine and the glial toxicants acrylamide and chloroquine. In some experiments the L-type voltage calcium channel blocker Nifedipine was employed. [Ca 2+ ] i was measured in populations of the cells using Fura-2AM and a charge coupled device (CCD) camera attached to a fluorescence microscope. dBcAMP induced both dose- and time-dependent changes in [Ca 2+ ] i with increases in both the [Ca 2+ ] i oscillations and mean [Ca 2+ ] i (e.g. in C6 cells at 18 min mean [Ca 2+ ] i was 318 ± 20nM following the single differentiating dBcAMP pulses, 489 ± 17nM (p < 0.001) following two serial pulses, and 275 ± 30nM (not significant) following three pulses). Therapeutic doses of fluoxetine and amitriptyline caused increases in the calcium oscillations and the mean calcium concentrations (maximum recorded mean increase was in the C6 cells at 10min by 0.02 μM fluoxetine when [Ca 2+ ] i was 411 ± 35nM c.f. control 254 ± 25nM, p = 0.01). Higher (non-therapeutic) doses of both antidepressants caused significant reductions. Chloroquine and acrylamide also caused dose-dependent bi-phasic types of alterations in [Ca 2+ ] i , with significant reductions at lower, sub-cytotoxic doses followed by significant increases at higher concentrations, approaching those which cause cell damage. Nifedipine treatment caused some reductions in the dBcAMP, antidepressant or toxicant-induced calcium changes, but this substance also initiated cytotoxic alterations. The findings show that both the activation-type changes (which are frequently associated with increased protective capacities) and toxic responses of C6 and 1321N1 cells to different chemical agents are associated with dose-dependent alterations in [Ca 2+ ] i .